2010
DOI: 10.1038/jid.2010.67
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Altered Wnt Signaling in Psoriatic Skin

Abstract: The Wnt gene family encodes a set of highly conserved secreted signaling proteins that have major roles in embryogenesis and tissue homeostasis. Yet the expression of this family of important mediators in psoriasis, a disease characterized by marked changes in keratinocyte growth and differentiation, is incompletely understood. We subjected 58 paired biopsies from lesional and uninvolved psoriatic skin and 64 biopsies from normal skin to global gene expression profiling. WNT5A transcripts were up-regulated 5-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
133
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 60 publications
11
133
1
1
Order By: Relevance
“…Several studies reported that the global Wnt signaling pathway or expression of some specific Wnt proteins was altered in psoriasis patients (8,10,42,43). In fact, a gene-expression study of 58 patients with psoriasis and 64 normal healthy controls by microarray showed that WIF1 was the most strongly downregulated gene in psoriatic skin versus normal skin (44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported that the global Wnt signaling pathway or expression of some specific Wnt proteins was altered in psoriasis patients (8,10,42,43). In fact, a gene-expression study of 58 patients with psoriasis and 64 normal healthy controls by microarray showed that WIF1 was the most strongly downregulated gene in psoriatic skin versus normal skin (44).…”
Section: Discussionmentioning
confidence: 99%
“…More microarrays demonstrated that Wnt5a was increased in psoriatic plaques of patients, indicating that the noncanonical Wnt signaling pathway might be activated in psoriasis (8,43). Despite the controversial findings of whether the canonical or noncanonical Wnt pathway was activated in psoriasis (9,10,42), all of the studies pointed out that the expression of inhibitory factors related to Wnt signaling, such as SFRP, Dkk, and WIF, were reduced to some extent in psoriasis (8,10). In the current study, we found that the expression of SFRP4, a negative modulator of Wnt signaling (45), was decreased in lesional skin of psoriasis mouse models and patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 19 mammalian homologues have distinct expression patterns in embryonic and adult tissues and their during infections with mycobacteria, Gram-negative and Grampositive bacteria [2][3][4][5][6], and chronic inflammation in rheumatoid arthritis, atherosclerosis, obesity, and psoriasis [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%